Analycis of Promotion Strategy at UMKM Kicimpring Yanma Cikondang Ganeas - Puspasari, Dewi; Aryanti, Ai; Pajrin, Salma Sopariatul; Rahmawati, Wati (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2026)
This study aims to assess the marketing tactics utilized by UMKM Kicimpring Yanma Cikondang in promoting and expanding the market reach of its traditional snack products. A qualitative descriptive approach was used to collect data through interviews, observations, and documents involving the owner and marketing team. The findings show that the business heavily relies on digital marketing through Instagram, TikTok, Facebook, WhatsApp, and e-commerce platforms, enhanced by word-of-mouth, which remains highly influential in influencing purchasing decisions. Additional promotional activities include sales promotion strategies such as the “Friday Blessing” sale, participation in UMKM expos, collaborations with influencers, and product sampling events. Packaging and customer feedback play a crucial role in improving brand perception and attracting customers. In spite of its marketing efforts, the UMKM faces multiple challenges, including a lack of funds for paid promotions, inconsistent product sales that require consignment strategies, and the incomplete utilization of educational resources in digital marketing. Customer responses to the ongoing promotional activities are largely positive, as indicated by increased sales and repeat purchases. To enhance future marketing results, the company intends to optimize creative content creation, leverage trending phenomena on TikTok, and boost participation in UMKM events and seasonal market campaigns. Overall, the implemented promotional tactics have contributed to increasing product visibility and attracting consumers, but further improvements are required to maximize competitiveness.